中小學教師工作壓力與因應策略相關性之後設分析：多向度的觀點 A Meta-analysis of the Correlation between Job Stress and Copying Strategies for Elementary and Secondary Teachers: A Multi-Dimensional Perspective - 陳瑋婷 Chen, Wei-Ting (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2010)
為了解國內中小學教師在不同層面工作壓力與因應策略之相關性，本研究針對43 篇研究報告共19,299 位研究對象進行後設分析。結果發現中小學教師總體工作壓力與總體因應策略之加權平均效應量為.10，屬於低效應量。中小學教師總體工作壓力與因應策略分向度的相關程度，由高而低依序為消極逃避、延宕處理、尋求支持及問題解決等四項策略。而中小學教師的工作負荷及人際關係等工作壓力，也分別與總體因應策略具有顯著正相關。除此之外，經同質性考驗後發現，各主題之效應量間存有變異。「總體工作壓力與總體因應策略相關性」、「總體工作壓力與消極逃避因應策略相關」、「總體工作壓力與延宕處理因應策略相關性」、「工作負荷壓力與總體因應策略相關性」及「人際關係與總體因應策略相關性」等主題之組內效應量，因任教階段變項之調節作用影響而有變異。而「總體工作壓力與總體因應策略相關性」、「總體工作壓力與消極逃避因應策略相關性」、「總體工作壓力與問題解決因應策略相關性」及「工作負荷壓力與總體因應策略相關性」等主題之組內效應量，受擔任職務變項之調節作用影響而有變異。 A meta-analysis of 43 studies (N = 19,299 participants) was conducted to determine the magnitude of correlation between job stress and copying strategies for elementary and secondary teachers from a multi-dimensional perspective. Across included studies on the correlation between overall job stress and overall copying strategies, the weighted mean effect size was .10. Besides, the correlation between overall job stress and negative avoidance, the correlation between overall job stress and putting it away awhile, and the correlation between overall job stress and seeking for support are significant and positive. The correlation between overall job stress and problem solving are not significant. The correlation between work loading and overall copying strategies and the correlation between interpersonal stress and overall copying strategies are also significant and positive. Additionally, the tests of homogeneity of most topics were statistically significant. Elementary versus secondary teachers was found to be significant moderator on the correlation between overall job stress and overall copying strategies, that between overall job stress and negative avoidance, that between overall job stress and putting it away awhile, that between work loading and overall copying strategies, and that between interpersonal stress and overall copying strategies. The position held was also a significant moderator on the correlation between overall job stress and overall copying strategies, that between overall job stress and negative avoidance, that between overall job stress and problem solving, and that between work loading and overall copying strategies.